رد الاعتبار للمحكوم عليه دراسة مقارنة بين الفقه الاسلامي والقانون لبجزائري - تجاني, أميرة (University of eloued جامعة الوادي, 2016)
The main objective of this research is the definition of one of the specific legal topics which is the subject of rehabilitation in Islamic jurisprudence and the Algerian law, so found out that the rehabilitation of the convicted is a system that aims to erase the effects of the criminal final judgment and remove all of its effects , that's why most of the legislation in the world moving to pay attention and subsequent care for convicts, because the Offender who has committed an offense needs care during the implementation of his Punishment and after implementation in order to return a useful member of society, such as, he needs to take care of him when he finished the implementation, in order to live with dignity and rights in their communities And the system of rehabilitation does not exist with this name in Islamic jurisprudence, however, this research aims to compare the fixed concepts in Islamic jurisprudence with the principles of rehabilitation system in Algerian law. This research includes in the first chapter the definition of rehabilitation concept, its types and its conditions of ,then the second chapter consists of the provisions of rehabilitation and its procedures , effects.
شريعة وقانون
Keywords: الفقهّ الإسلامي/المحكوم عليه/ ردّّالاعتبار; Islamic jurisprudence/convict/rehabilitation